Special Needs in Substance Use Treatment for Women Who Use Drugs: Social and Mental Health Factors - Antonio Jesús Molina-Fernández; Jesús Saiz-Galdos; Irene María Arribas-Tiemblo; Gisela Hansen-Rodríguez; Iván Sánchez-Iglesias; Elena Ayllón-Alonso; Banesa Mena-García (Women)
Women who receive substance use treatment have a particular classification of sensitivity to European drugs and drug use (according to the EMCDDA). The average level of women’s treatment is lower than men’s across Europe, while women’s abandonment is higher than men’s. The purpose of this study was to examine the factors associated with problems for women who use drugs, analyzing several psychological and social factors (gender, substance use, mental health, source of economic support, legal status, and abuse). Methodology: This was a quantitative study. Data on 2179 people receiving rehabilitation treatment were obtained from the EuropASI survey. The dependent variables in this study were (1) a patient’s known history of addiction and mental illness; (2) primary drug use; (3) drug use in their lifetime and the past month; (4) mood in their lifetime and the past month, physical condition, and sexual abuse history; (5) mental illness in their lifetime and the past month (including suicide attempts); (6) legal status in their lifetime and the past month; (7) and source of income in the past month and (8) and the number of patients. The factor of gender was taken as a dichotomous variable (male–female). The confidence interval used was 95%. Results: In summary, we found that women had consumed more alcohol, used more drugs, and suffered more from depression, anxiety, and suicidal ideation than men, both during their lifetimes and in the past month. In addition, women were more likely than men to be stigmatized for prostitution because their financial support came mainly from colleagues, friends, and family, as well as from prostitution. Finally, women had experienced more violence (emotional, physical, and sexual) during their lifetimes and in the last month than men. Conclusion: There appears to be a need to develop a comprehensive treatment network for addictive behaviors from a multifactorial perspective, including harm reduction, psychosocial support, and recovery programs; furthermore, targeting specific groups with special needs, such as women, especially those with mental health problems, women with alcoholism, and abused women, it also seems important to develop adaptive recovery programs within addictive behavior treatment networks.